Formation mechanism of multiple spallation and its penetration induced by shear localization in NiTi alloy under implosion loading - Xianye Wu; Xiaoyang Pei; Xiang Chen; Hao Zhang; Jin Wang; Xin Yang; Meizhen Xiang; Shang Gao; Fang Wang (Matter and Radiation at Extremes)
This study uses nonequilibrium molecular dynamics simulations to explore the dynamic failures and deformation mechanisms of a cylindrical shell composed of nanocrystalline nickel–titanium alloy under implosion loading. We discover that some individual spall planes are sequentially generated in the material along the propagation of a radial stress wave, indicative of the formation of multiple spallation. For larger grain sizes, void nucleation at the first spallation occurs in a coexisting intergranular/transgranular manner, whereas with decreasing grain size, voids tend to nucleate along the grain boundaries. Correspondingly, the spall strength exhibits a transition from an inverse Hall–Petch to a Hall–Petch relationship. For larger grain sizes, at the secondary spallation, localized shearing zones and grain boundaries provide potential void-nucleated sites. Importantly, the formation of shear deformation bands promotes grain refinement, contributing to a reduction in the dislocation-induced strengthening effect. Consequently, a lower spall strength is produced, in contrast to the first spallation. As the grain size becomes smaller, voids nucleate mostly along grain boundaries, and plastic deformation is dominated by dense grain boundaries. Overall, the high temperature caused by shear localization leads to material weakening, and in turn there is a significant decrease in the spall strength for the secondary spallation, compared with the first. Finally, significant penetration between two spall planes is observed for large grain size, which can be attributed to the nucleation of voids on linking grain boundaries, with temperatures exceeding the melting point of the material.